2008
DOI: 10.1016/j.metabol.2008.02.016
|View full text |Cite
|
Sign up to set email alerts
|

High-fat, energy-dense, fast-food–style breakfast results in an increase in oxidative stress in metabolic syndrome

Abstract: The metabolic syndrome (MetS) is associated with an increased incidence of diabetes and coronary heart disease. Postprandial lipemia is a prominent feature of dyslipidemia in both type 2 diabetes mellitus and MetS and is also associated with coronary heart disease. Oxidative stress and inflammation are pivotal in all stages of atherosclerosis; however, there is a paucity of data on postprandial oxidative stress and inflammation in subjects with MetS. Thus, the primary aim of this study was to compare the postp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(99 citation statements)
references
References 18 publications
2
95
0
2
Order By: Relevance
“…37 Another cross-sectional study also reported that dietary energy density was an independent predictor of obesity, elevated fasting insulin levels, and the metabolic syndrome in adults. 38 High content of fats, cholesterol, saturated and trans fatty acids in fast foods also considered as threatening factor could lead to postprandial metabolic disorders including dyslipidemia, subclinical inflammatory process and oxidative stress, 39 and also long term abdominal fat gain, insulin resistance and hypertension. [40][41][42][43] While consumption of 5 grams trans fat per day may increase the risk of ischemic heart disease up to 25%, the trans fatty acid content of only one fast food meal was reported several times of recommended amount by dietary guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…37 Another cross-sectional study also reported that dietary energy density was an independent predictor of obesity, elevated fasting insulin levels, and the metabolic syndrome in adults. 38 High content of fats, cholesterol, saturated and trans fatty acids in fast foods also considered as threatening factor could lead to postprandial metabolic disorders including dyslipidemia, subclinical inflammatory process and oxidative stress, 39 and also long term abdominal fat gain, insulin resistance and hypertension. [40][41][42][43] While consumption of 5 grams trans fat per day may increase the risk of ischemic heart disease up to 25%, the trans fatty acid content of only one fast food meal was reported several times of recommended amount by dietary guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…After consumption of an energy-dense (i.e. high-fat) diet, plasma HNE levels increase rapidly and significantly within minutes (Devaraj et al, 2008). When consumed regularly, this diet promotes obesity, which suggests a role for HNE very early in the development of obesity.…”
Section: Lipid Peroxidation By-products Association With Obesitymentioning
confidence: 99%
“…The postprandial state is a stressful condition in which an increase in oxidative stress takes place (Cardona et al 2008;Devaraj et al 2008;Ursini and Sevanian 2002). Postprandial oxidative stress is characterized by an imbalance between the production of ROS and their elimination by the antioxidant system (Durackova 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Postprandial oxidative stress is characterized by an increase in oxidative stress biomarkers after the intake of a meal (Cardona et al 2008;Devaraj et al 2008;Ursini and Sevanian 2002), which is extremely important, as humans spend most of their time in the postprandial state (de Koning and Rabelink 2002). In line with this, we previously demonstrated that a MUFA-rich diet improves plasma postprandial oxidative stress parameters compared to an SFA-rich diet, and that low-fat diets have an intermediate effect relative to the MUFA-rich and SFA-rich diets (PerezMartinez et al 2010).…”
Section: Introductionmentioning
confidence: 99%